NATIONAL PERSPECTIVE: Q&A WITH NATIONAL FEDERATION OF THE BLIND & ASSOCIATION OF HIGHER EDUCATION AND DISABILITY - Betts, Kristen (Online Learning, 2013)
Student success for online students with disabilities requires an institutional commitment to accessibility. It also requires an understanding of the benefits and opportunities as well challenges and barriers related to online learning. This question and answer session provides a national perspective from the National Federation of the Blind (NFB) and the Association of Higher Education And Disability (AHEAD) on online learning, accessibility, and students success. Organizational representatives for this session include Mark Riccobono, the Director of the Jernigan Institute, NFB, and Kelly Hermann, Chairs of AHEAD’s Special Interest Group on Online and Distance Learning.